Altered expression of surface alpha-1,3-glucan in genetically related strains of Blastomyces dermatitidis that differ in virulence. - Hogan, L H (1994)
Recent studies of the dimorphic fungal pathogens Histoplasma capsulatum and Paracoccidioides brasiliensis have suggested a role in virulence for the cell surface carbohydrate alpha-(1,3)-glucan. To investigate a possible basis for alpha-(1,3)-glucan in the pathogenicity and virulence of the dimorphic fungus Blastomyces dermatitidis, we examined three genetically related strains of B. dermatitidis that differ in their virulence for mice: wild-type virulent strain ATCC 26199; mutant strain ATCC 60915, which is 10,000-fold reduced in virulence; and mutant strain ATCC 60916, which is avirulent. Immunologic quantitation of cell wall alpha-(1,3)-glucan revealed that the mutant yeasts were almost devoid of this sugar moiety, in contrast to the high concentration of alpha-(1,3)-glucan on the cell wall of the wild-type yeasts. These differences are discussed in relation to previous studies of yeast surface expression of the WI-1 antigen and recognition and binding of the related strains by human monocyte-derived macrophages.